Biologically Inspired Cognitive Architectures 2010 - Samsonovich, Alexei V. (IOS Press, 2013)
This book presents the proceedings of the First International Conference on Biologically Inspired Cognitive Architectures (BICA 2010), which is also the First Annual Meeting of the BICA Society (http://bicasociety.org). A cognitive architecture is a computational framework for the design of intelligent, even conscious, agents. It may draw inspiration from many sources, such as pure mathematics, physics or abstract theories of cognition. A biologically inspired cognitive architecture (BICA) is one which incorporates formal mechanisms from computational models of human and animal cognition, which currently provide the only physical examples with the robustness, flexibility, scalability and consciousness that artificial intelligence aspires to achieve. The BICA approach has several different goals: the broad aim of creating intelligent software systems without focusing on any one area of application; attempting to accurately simulate human behavior or gain an understanding of how the human mind works, either for purely scientific reasons or for applications in a variety of domains; understanding how the brain works at a neuronal and sub-neuronal level; or designing artificial systems which can perform the cognitive tasks important to practical applications in human society, and which at present only humans are capable of. The papers presented in this volume reflect the cross-disciplinarity and integrative nature of the BICA approach and will be of interest to anyone developing their own approach to cognitive architectures. Many insights can be found here for inspiration or to import into one’s own architecture, directly or in modified form.